Is hyperglycemia the only risk factor for implant in type 2 diabetics during the healing period? - Tang, Dezheng; Wang, Entang; Xu, Yifan; Liang, Chao; Liu, Changying; Lin, Xiao; Li, Jun (Oral diseases, 2021)
Objective To determine whether risk factors other than hyperglycemia lead to failed osseointegration in patients with type 2 diabetes mellitus (T2DM) during the healing period. Materials and Methods We compared the success rates between patients with and without T2DM during the healing period at our center. Bone marrow mesenchymal stem cells (BMSCs) were cultured from subjects. Proteomics was used to detect differentially expressed proteins (DEPs) among the DM failure (DM‐F), DM success (DM‐S), and control (Con) groups. The correlation between the expression levels of nine target DEPs and medium glucose concentrations was investigated. Results Higher failure rates were observed in the T2DM patients. Fifty‐two DEPs were found between the DM‐F and DM‐S groups. Seventy‐three DEPs were found between the DM‐F and Con groups. Forty‐three DEPs were found between the DM‐S and Con groups. Five target DEPs were expressed at the same levels in the medium with different glucose concentrations. Gene ontology annotation and functional enrichment analysis suggest that the DEPs detected in the DM‐F group may affect the biological function and regulatory potential of BMSCs. Conclusions The DEPs detected in the DM‐F group can be intervention targets for to prevent implant failure in T2DM patients. Risk factors besides hyperglycemia may affect osseointegration during healing period.